Pengaruh Subtitusi Tepung, Daun Kelor dan Tulang Ikan Tembang terhadap Sifat Fisikokimia dan Daya Terima Biskuit - Ira Yunita Nuhalawang; Anna Henny Talahatu; Marselinus Laga Nur (Media Kesehatan Masyarakat, 2021)
Kelor plants may be an alternative to a potential source of protein and calcium to satisfy the need for nourishment in pregnant mothers and infants. Food diversification can be made by making foods that contain high calcium from the calcium intake contained in fish bones. Pregnant women are one group that is very at risk of experiencing malnutrition. During pregnancy, the need for nutritional intake increases, but it is not balanced with the consumption of sufficient nutritious food. Kelor-processing development with the addition of fish bones may be an alternative to the treatment of nutrient deficiency problems mainly in pregnant mothers and infants. This study aims to determine the effect of adding Moringa leaf flour with tembang fish bone meal to the physicochemical properties and acceptability of biscuits. The research conducted was an experimental study using factorial completely randomized design (CRD), namely conducting an experiment in making biscuits with wheat flour as a base ingredient by adding Moringa leaf flour and fishbone meal with treatment levels of 0%, 10%, 20% and 30%. The results showed that the addition of Moringa leaf flour with tembang fish bone meal had an effect on calcium (p=0,00), phosphorus content (p=0,00), moisture content (p=0,520), ash content (p=0,00), hardness test (p=0,152), taste (p=0,00), aroma (p=0,00) and texture (p=0,043), and had no effect on color (p=0,743) acceptability. For further researchers it is recommended to continue further research with other nutritional content related to meeting the nutritional needs of pregnant women, breastfeeding mothers and infants as well as all circles of society.